Revitalization of The Collection of Zakat Funds in Indonesia: An Explanation from Yusuf Al-Qaradawi's Fiqh Al-Zakah - Akmal Ihsan; Armi Agustar; Azis Muslim; Muhammad Adnan Azzaki (Department of Islamic Economics, Islamic University of Indonesia, 2022)
This study analyzes the government's role in collecting zakat funds in Indonesia based on Yusuf Qaradawi’s thought in his Fiqh al-Zakah. The study uses descriptive qualitative method with a case study approach. Government policies in collecting zakat funds need to be revitalized because the results obtained are still far from the set targets. The government must issue new policies so that the efficient collection of zakat can help the country and achieve benefits of its people. To achieve this goal, Yusuf Qardhawi offers several policies for the government, evaluating the amendments to zakat management regulations. In the book of fiqh al-zakah, Yusuf Qardhawi emphasizes that the govern-ment not only focuses on voluntary zakat but also pays attention to paying zakat physically and men-tally. The government must collect zakat from material (al-a'yan) owned by Muslims. Furthermore, the government must also deduct or collect zakat directly from the savings of the Muslim community in banks if they have reached the nisab and haul. This is done to achieve the potential target of zakat in Indonesia. In addition, the government also helps people to abort their obligations as Muslims. With this policy, Yusuf Qardhawi believes that the collection of zakat can run well and efficiently so that it has a real impact on the nation in general and Muslims.